Representation of prophetic value of digital children's literature Nussa dan Rara series as character education learning media - Budiana, Nia; Pulungan, Alpi Anwar; Tamphu, Sainee (Diksi, 2025)
Children's literature has a big role in determining the development of a child's personality to reach maturity. One type of children's literature packaged in digital form is electronic stories, such us Nussa dan Rara series. The purpose of this study was to describe and interpret the prophetic value of children's literature from Nussa dan Rara series as a medium for character learning in children. The research method used in this study was a descriptive qualitative method. The research data was taken from Nussa dan Rara series, especially from the episode Gratis Pahala. Data collection in this study was carried out by (1) recording, (2) transferring in written form, and (3) classifying the data. The data analysis technique was content analysis with the help of Kuntowijoyo's prophetic literary theory which consists of humanization, liberation, and transcendence. The results of this study are the discovery of representations of humanization in children's lives, liberation in the perspective of inclusion, and transcendence between children and religiosity. Humanization in this story is sensitive, caring, patient, and forgiving. Liberation can be seen in terms of equality between children with disabilities and normal children. Children with disabilities have the right to receive good and not arbitrary treatment from the surrounding community. The value of transcendence appears in the form of the teachings of the Prophet and the Qur'an.